Global Entrepreneurship and Development Index 2018 - Ács, Zoltán J. (SpringerBriefs in Economics,, 2018)
This brief presents a detailed look at the entrepreneurial ecosystem of nations around the world by combining individual data with institutional components. Presenting data from the 2018 Global Entrepreneurship and Development Index (GEDI), which measures the quality and scale of entrepreneurial process from 137 countries world-wide, this book provides a rich understanding of entrepreneurship and a more precise means to measure it. The novelty of the GEDI 2018 edition is the examination of the connection between the GEDI score and the computed total factor productivity (TFP) values. The Global Entrepreneurship and Development Index is an annual index (composite indicator) that measures the health of the entrepreneurship ecosystems in a given country. The authors have identified 14 components (or pillars) that are important for the health of entrepreneurial ecosystems, identified data to capture each , and used this data to calculate three levels of scores for a given country: the overall GEDI score, scores for Individuals and Institutions, and pillar level scores (which measure the quality of each of the 14 components). .